2008
DOI: 10.1037/1040-3590.20.3.238
|View full text |Cite
|
Sign up to set email alerts
|

Malingering as a categorical or dimensional construct: The latent structure of feigned psychopathology as measured by the SIRS and MMPI-2.

Abstract: The 6 nonoverlapping primary scales of the Structured Interview of Reported Symptoms (SIRS) were subjected to taxometric analysis in a group of 1,211 criminal and civil examinees in order to investigate the latent structure of feigned psychopathology. Both taxometric procedures used in this study, mean above minus below a cut (MAMBAC) and maximum covariance (MAXCOV), produced dimensional results. A subgroup of participants (n = 711) with valid Minnesota Multiphasic Personality Inventory-2 (MMPI-2) protocols we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 45 publications
3
16
2
1
Order By: Relevance
“…The parameter p(z i | D) therefore indicates the theoretical position of each participant's performance along a continuum of effort (see Iverson, 2010, p. 110). This feature of our Bayesian latent group model is consistent with recent views that consider effort and malingering as continua rather than taxonomies (see Iverson, 2010;Walters et al, 2008;Walters, Berry, Lanyon, & Murphy, 2009). We believe that providing individual posterior classification estimates of effort constitutes another advantage of the proposed model.…”
Section: Discussionsupporting
confidence: 85%
“…The parameter p(z i | D) therefore indicates the theoretical position of each participant's performance along a continuum of effort (see Iverson, 2010, p. 110). This feature of our Bayesian latent group model is consistent with recent views that consider effort and malingering as continua rather than taxonomies (see Iverson, 2010;Walters et al, 2008;Walters, Berry, Lanyon, & Murphy, 2009). We believe that providing individual posterior classification estimates of effort constitutes another advantage of the proposed model.…”
Section: Discussionsupporting
confidence: 85%
“…reported that taxometric analyses of results from psychiatric outpatients completing a health inventory with embedded validity scales indicated that feigning of physical symptoms was dimensional, not categorical. Similarly, Walters et al (2008) analyzed Minnesota Multiphasic Personality Inventory 2nd Edition (MMPI-2) and Structured Inventory of Reported Symptoms (SIRS) data from forensic neuropsychiatric evaluees and found evidence for feigned psychiatric symptoms as a continuous, not a categorical phenomenon. Finally, analyzed results on objective neurocognitive feigning instruments in forensic neuropsychiatric patients and reported evidence for a dimensional structure of the construct.…”
Section: Conceptual Concernsmentioning
confidence: 99%
“…Since the MMPI-2 is the most popular and well- researched objective clinical assessment instrument [30], the construct validity of the Chinese version of SIRS-2 was examined by using MMPI-2. The SIRS primary scales produced correlations with MMPI-2 feigning scales with inverse relations with its scales of Defensiveness.…”
Section: Discussionmentioning
confidence: 99%